Colleges of Education Lecturers’ Attitude Towards the Use of Virtual Classrooms for Instruction - Ekunola, Gbadebo Temitope; Onojah, Amos Ochayi; Talatu, Ahmed Fahdilat; Bankole, Moyosore Olakunle (Universitas Pendidikan Indonesia (UPI), 2022)
This study aimed at examining the attitudes of the college of education lecturers towards the use of VCs for instruction in Ondo State. The objectives were to: (i) examine lecturers’ attitude towards the use of VCs, (ii) determine the difference in lecturers’ gender on their attitude towards the use of VCs, and (iii) examine lecturers’ attitude towards the use of VCs based on years of teaching experience. A self-structured questionnaire with a reliability result of 0.70 was used to collect data from 298 lecturers. Frequency counts, percentages, and mean were used to answer research question 1, and an independent sample t-test was used to test hypotheses 1-2 at a 0.05 level of significance. It was revealed that lecturers had a positive attitude towards the use of VCs, no significant difference in the lecturers’ attitude towards the use of VCs based on gender and there was a significant difference between the less experienced and the experienced lecturers' attitudes towards the use of VCs in favor of less experienced lecturers. The study concluded that irrespective of gender, lecturers’ attitudes towards the use of VCs do not vary, while there are disparities in the lecturers' years of teaching experiences, this implied that, regardless of the instructors' gender, integrating VCs for education will be a welcome development. While lecturers’ attitude is influenced by their years of teaching experience. The study recommended among others that concerned agencies and school management should sensitize, train, and provide an enabling environment.